Jejak Budaya Lokal Dalam Perkembangan Semarang Night Carnival 2011–2022 - Putri, Melody Aria; Susilowati, Endang; Puguh, Dhanang Respati (PURBAWIDYA, 2025)
This article explores the Semarang Night Carnival (SNC) as a means of cultural preservation and a reinforcement of the local identity of Semarang City within the realms of tourism and the creative industry. Since its inaugural event in 2011, SNC has developed into an annual cultural festival featuring costumes with local and national cultural themes presented through costume parades and visual narratives. This study employs a descriptive qualitative approach with historical methods, utilizing primary and secondary data in the form of archives, documentation, interviews, and scholarly references. The findings reveal that SNC is not merely a performance but also serves as a medium for education, cultural promotion, and the empowerment of local artists and costume artisans. Themes such as Warak Ngendog, Paras Semarang, Kemilau Nusantara, and Trilogy serve as visual representations of harmony, acculturation, and the richness of local culture. Strengthening cultural events based on local wisdom can be an effective strategy to enhance the city’s image, increase tourism appeal, and foster a sustainable creative economy ecosystem.